Association between exposure to perfluoroalkyl and polyfluoroalkyl substances with estimated glomerular filtration rate: Mediating role of serum albumin - Hua Fang; Huajing Chang; Danjing Chen; Wenxin Qiu; Jiangwang Fang; Yunli Wu; Xian-E. Peng (Ecotoxicology and Environmental Safety)
Background: Previous studies have demonstrated perfluoroalkyl and polyfluoroalkyl substances (PFAS) impact renal function, with albumin playing dominant role in their transport and accumulation. However, the mediating role of albumin in PFAS-induced renal impairment and the identification of sensitive populations remain uninvestigated. Methods: This study included 9328 individuals from NHANES 1999–2018 with data on serum PFAS, creatinine, albumin, and covariates. The estimated glomerular filtration rate (eGFR) was calculated using standardized creatinine. Associations between perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonate (PFHxS), and perfluorononanoic acid (PFNA) with eGFR and the risk of decreased renal function (eGFR < 90 vs. eGFR ≥ 90) using linear and logistic regression, weighted quantile sum (WQS) regression, Bayesian kernel machine regression (BKMR), and restricted cubic spline (RCS) analyses. Subgroup analyses identified sensitive populations. Mediation analysis was performed to examine the mediating role of albumin. Comparative toxicology databases identified relevant genes for mechanistic exploration. Results: Ln-transformed PFOA (β = −1.91, 95 % CI: −2.82 to −1), PFOS (β = −1.48, 95 % CI: −2.19 to −0.78) and PFHxS (β = −0.94, 95 % CI: −1.65 to −0.23) were negatively correlated with eGFR. PFOA (aOR = 1.21, 95 % CI: 1.1–1.32), PFOS (aOR = 1.2, 95 % CI: 1.12–1.29), and PFHxS (aOR = 1.13, 95 % CI: 1.05–1.21) were positively correlated with the risk of decreased renal function. Subgroup analyses indicated that individuals ≤ 45 years, females and other races were more sensitive. Albumin mediated 18.2 %, 16.4 %, 29.8 %, and 18.7 % of the negative effects of PFOA, PFOS, PFHxS, and PFNA on eGFR, respectively. Functional enrichment analysis suggested PFAS impair renal function by affecting lipid metabolism and increasing oxidative stress. Conclusions: PFAS exposure is negatively associated with eGFR and positively associated with the risk of decreased renal function, with albumin playing a partial mediating role.